Considerações para traduzir "Grande sertão: veredas" para Libras - Sutton-Spence, Rachel (Revista da Anpoll, 2018)
This essay provides an annotated translation with commentary of the title and opening three short sentences of João Guimarães Rosa’s “Grande Sertão: Veredas” from Portuguese into Brazilian Sign Language, Libras. A Libras translation uses elements of space and highly iconic structures to recreate the story is a visual form. The commentary here considers the challenges involved in translating the brief section of the Portuguese text, including accommodation of deaf literary norms to those of contemporary Brazilian society, the search for appropriate Libras signs for the regionally specific context of the novel, the needs of a deaf audience to see the visual aspects of the story, and the decisions made on how to represent GuimarãesRosa’s idiosyncratic style of Portuguese in Libras. It highlights the importance of the sign language translator working as a “translator-actor” where the written text told in first person is translated into Libras, producing a translation that is embodied and presented by the translator, who takes the role of the narrator’s “I”.